Efektifitas Pembelajaran Ekonomi Islam Di STIE Ahmad Dahlan Jakarta - Yayat Sujatna (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2012)
The development of Islamic financial institutions, especially Islamic banking is fast enough not matched by a competent human resources. This study aims to determine the effectiveness of the learning of Islamic economics in STIE Ahmad Dahlan Jakarta, which in turn can meet the needs of human resources. Methods used in this study was descriptive qualitative. The results showed that the learning of Islamic economics is good and effective.